2018
DOI: 10.1002/jcp.27574
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA SLC8A1‐AS1 protects against myocardial damage through activation of cGMP‐PKG signaling pathway by inhibiting SLC8A1 in mice models of myocardial infarction

Abstract: Extensive investigations into long noncoding RNAs (lncRNAs) in various diseases and cancers, including acute myocardial infarction (AMI) have been conducted. The current study aimed to investigate the role of lncRNA solute carrier family 8 member A1 antisense RNA 1 (SLC8A1‐AS1) in myocardial damage by targeting solute carrier family 8 member A1 (SLC8A1) via cyclic guanosine 3′,5′‐monophosphate‐protein kinase G (cGMP‐PKG) signaling pathway in AMI mouse models. Differentially expressed lncRNA in AMI were initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 45 publications
(70 reference statements)
0
25
0
Order By: Relevance
“…Recently, Guo et al showed that LINC00528 was one of the most upregulated lncRNA in MI tissues compared to normal tissues [15]. Zhou et al revealed that LINC00528 was one of the most upregulated lncRNA in CHD tissues compared with normal tissues [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Guo et al showed that LINC00528 was one of the most upregulated lncRNA in MI tissues compared to normal tissues [15]. Zhou et al revealed that LINC00528 was one of the most upregulated lncRNA in CHD tissues compared with normal tissues [14].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs have been highlighted as key factors in the progression of AMI. Recently, studies showed that LINC00528 was one of the most upregulated lncRNA in coronary heart disease [14,15]. However, the roles and underlying mechanisms of LINC00528 in MI remain unclear.…”
Section: Linc00528 Expression In MImentioning
confidence: 99%
“…LncRNA AK088388 was reported to promote autophagy via direct binding of miR-30a to affect myocardial I/R injury [10]. Xu et al reported that lncRNA SLC8A1-AS1 could activate the cGMP-PKG signaling pathways to protect myocardial damage in mouse MI model [11]. Moreover, down-regulation of lncMIRT1 improved the I/R-induced injury in aged diabetic rat model though inhibition of NFκB signaling pathway [12].…”
Section: Introductionmentioning
confidence: 99%
“…LncRNA SLC8A1-AS1 is oriented in an antisense direction to the protein-coding gene SLC8A1, which is located on chromosome 2 of the human genome [14]. SLC8 gene is a member of CaCA (Ca 2+ /Cation Antiporter) superfamily, encoding Na + /Ca 2+ exchangers (NCX), mainly expressed on cell membrane, mediate Na + /Ca 2+ uxes across the cell-membrane.…”
Section: Discussionmentioning
confidence: 99%